Catherine Perryman: capstone - Perryman, Catherine, artist (Colorado State University. Libraries, 2024)
The artist's statement: My work is an exploration of the body, both physical and psychological. I build in many ways, but primarily with coils. Making in this way speaks to the tension between control and surrender, and the ways in which clay is shaped and stretched by both external forces and the internal impulses of the artist. The coil, a simple and repetitive form. Coils themselves are not complicated, though I derive complex sensation while building with them. The hand rolling and guiding the coil, each layer binding to the next, mirrors the ongoing construction of identity, memory, and social influence. Each coil represents a part of the whole—incremental, vulnerable, and, at times, uncertain. Like a body, the coils form connections, whether they are stacked or smeared, layered or unraveled, pushing against themselves to form a unified structure. The physical act of coiling is a metaphor for the larger forces that shape and condition us, whether societal or internal. There is an intimacy in the way the coils are built, as they grow, curve, and twist, responding to the hand that shapes them. But there is also tension: a cost to the process, a push and pull between autonomy and external influence. Just as bodies are shaped by culture, time, and circumstance, so too are the coils shaped by the hands that build them.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery